2019
DOI: 10.3390/ijerph16234787
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent Types of Intracranial Hemorrhage are Associated with a Higher Mortality Rate in Adult Patients with Traumatic Subarachnoid Hemorrhage: A Cross-Sectional Retrospective Study

Abstract: Traumatic subarachnoid hemorrhage (SAH) is the second most frequent intracranial hemorrhage and a common radiologic finding in computed tomography. This study aimed to estimate the risk of mortality in adult trauma patients with traumatic SAH concurrent with other types of intracranial hemorrhage, such as subdural hematoma (SDH), epidural hematoma (EDH), and intracerebral hemorrhage (ICH), compared to the risk in patients with isolated traumatic SAH. We searched our hospital’s trauma database from 1 January, 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…Increased posttraumatic diffuse cerebral edema mortality reflected diffuse brain injury and decreased cerebral perfusion, resulting from increased ICP. Traumatic SAH indicates increased head injury severity and is a well-established poor prognostic factor [26]. The significantly short hospital stay for cerebral edemas found here is likely related to poor survivability and early death among them.…”
Section: Discussionmentioning
confidence: 65%
“…Increased posttraumatic diffuse cerebral edema mortality reflected diffuse brain injury and decreased cerebral perfusion, resulting from increased ICP. Traumatic SAH indicates increased head injury severity and is a well-established poor prognostic factor [26]. The significantly short hospital stay for cerebral edemas found here is likely related to poor survivability and early death among them.…”
Section: Discussionmentioning
confidence: 65%
“…Previous literature has suggested that SAH is more predictive of TBI mortality when it occurs simultaneously with another tICH, such as SDH (17,18). We examined the mortality in subgroups of the SAH population, including SAH with concurrent SDH, SAH without SDH, and SAH without other tICH.…”
Section: Post-hoc Testsmentioning
confidence: 99%
“…A cross-sectional study of 1856 patients with TSAH found that patients with iTSAH had a 1.8% mortality rate, compared with patients with SAH + one diagnosis (7.9%), SAH + two diagnoses (12.4%), and SAH + three diagnoses (27.3%), where one, two, and three diagnoses indicated the existence of one, two, or three other types of intracranial hemorrhage (subdural hematoma, epidural hematoma, or ICH). 38 When controlling for sex, age, and pre-existing comorbidities, Group II, Group III, and Group IV patients had a 4.0, 8.9, and 21.1 times higher adjusted OR for death, respectively, than the patients with iTSAH.…”
Section: Review Findingsmentioning
confidence: 92%